Addressing Online Violence Against Women and Girls in the Commonwealth Asia Region: The Role of Bystanders - Secretariat, Commonwealth (Commonwealth iLibrary, 2023)
Online violence is increasing rapidly and is emerging as one of the biggest threats facing the online world today. Acts of online violence take multiple forms, including cyberstalking, cyberbullying, sexual harassment, sex trolling, doxing, hate speech, public shaming and intimidation. Broadly speaking, online violence against women and girls and the victimisation pattern in Commonwealth Asia member countries are consistent with the overall global trend. However, given unique formal and informal institutions in these countries, perpetration and victimisation related to OVAWG have many significant aspects that are different from most other countries in the world. As a result of underdeveloped regulations and regulatory infrastructure related to OVAWG, it is difficult to arrest, prosecute and convict the perpetrators in most of these countries. Meanwhile, societal norms tend to make victims of OVAWG feel devalued and excluded.